The association between interdental cleaning and periodontitis in an urban Thai adult cohort: a cross-sectional study - Panthira Aroonratana; Attawood Lertpimonchai; Lakshman Samaranayake; Prin Vathesatogkit; Lalitsara Thienpramuk; Kanoknadda Tavedhikul (BMC, 2024)
Abstract Background Plaque biofilm is a major etiologic factor of periodontitis, and its effective removal prevents or ameliorates the disease. However, toothbrushing alone does not sufficiently clean the interdental area, and additional interdental cleaning is required to completely remove the plaque from this locale. This cross-sectional study aimed to assess the association of interdental cleaning on the prevalence of periodontitis in a large urban Thai adult cohort. Methods Interdental cleaning data were retrieved from a dental survey of 1,743 employees of the Electricity Generating Authority of Thailand (EGAT) in 2019. The Centers for Disease Control and Prevention/American Association of Periodontology (CDC/AAP) periodontal case definitions were applied. The participants were subdivided into two groups as those with or without periodontitis depending on their oral health status assessed by calibrated professional examiners. The proportion of subjects who performed interdental cleaning was assessed through a self-reported questionnaire by frequency (daily/ ≥ 1 per week/ none) and profile (correct/ incorrect) of interdental cleaning. Then, the association between interdental cleaning and periodontitis was calculated using logistic regression analysis controlling for the common risk factors of periodontitis such as age, sex, education, smoking, and diabetes. Results Participants who performed interdental cleaning on a daily basis and ≥ 1 per week were 27.5% (95% CI: 25.4, 29.6) and 29.1% (95% CI: 27.0, 31.3), respectively while the remainder did not practice. Of those who used interdental cleaning, about one-half focused on sites with food impaction. There was a significant 44% lower prevalence of periodontitis (adjusted odds ratio of 0.56 (95%CI: 0.40, 0.79) in the cohort with a frequent and correct group. Conclusions Our data indicate an inverse association between interdental cleaning and periodontitis, particularly in those who routinely adhered to it. Regular interdental cleaning is likely to have a salutary effect on oral health. Trial registration The study was registered retrospectively in Thai Clinical Trials Registry, Registration number: TCTR20240817005, on 17 Aug 2024 ( https://www.thaiclinicaltrials.org ).